Service quality and the share of renewable energy in electricity generation. (April 2021) - Yao, Jingyuan; Xiao, Erliang; Jian, Xianzhong; Shu, Lingli
Abstract: The government's policy on the proportion of renewable energy in power generation significantly affects consumers and all companies. Few studies have considered the implications for service quality. A model based on the Stackelberg-game theory is developed to obtain the optimal strategies and profits of all companies in equilibrium. Contracts are proposed to help all agents maximize their profits. We find that when the government gradually increases the proportion of renewable energy generation, and the cost of renewable energy generation decreases, the changes in profits for all companies and electricity prices are minimal. Highlights: A model with service quality is developed to obtain the optimal strategies of the power companies. Two contracts are proposed to help the power companies maximize profits. The impacts of renewable energy share on power companies' profits and electricity prices is studied.